Pengaruh Kualitas Produk dan Pelayanan Terhadap Kepuasan Penghuni Blok Melati Rumah Susun Penjaringan - Ningsih, Fitria; Rini, Ratih Setyo (Jurnal Mnajemen | Ekonomi | Akuntansi, 2026)
The satisfaction of apartment residents is an important indicator in assessing the quality of urban housing, especially in densely populated areas like Penjaringan. This study aims to analyze the influence of product quality and service quality on resident satisfaction in Block Melati Apartment Penjaringan. The method used is quantitative with a statistical approach, involving 76 respondents as permanent residents. Data was collected through questionnaires using a Likert scale, and the sample calculation used Slovin's formula. The results of this study indicate that product quality and service quality have a positive effect on resident satisfaction. The validity test using Pearson correlation shows that all statement items are valid, with the calculated r greater than the r table (0.226). The reliability test with Cronbach’s Alpha shows that all variables are reliable: Product Quality (α = 0.827), Service Quality (α = 0.780), and Resident Satisfaction (α = 0.834), which meet the criteria above 0.70. These findings can provide input for apartment managers to improve the quality of housing through ongoing enhancements to products and services.